Tumor response and its impact on treatment failure in rectal cancer: does intensity of neoadjuvant treatment matter? - Diefenhardt, Markus; Martin, Daniel; Fleischmann, Maximilian; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Rödel, Claus; Fokas, Emmanouil (Cancers, 2024)
Objectives: Additional adjuvant treatment in patients with rectal cancer with limited response to neoadjuvant treatment to mitigate their higher risk of treatment failure remains controversial. Methods: This is a post hoc analysis of a cohort study of 3 randomized phase 2 or 3 trials (CAO/ARO/AIO-94, -04, and -12 trial) that included 1948 patients with locally advanced rectal adenocarcinoma. After excluding patients with missing information, 1788 patients (1254 men and 524 women; median age: 62.6 years, age range: 19-84 years) were eligible. We analyzed the extent of tumor response and its association with the incidence of treatment failure after different neoadjuvant treatment approaches. Results: Tumor response was significantly enhanced with more intensive neoadjuvant treatment. After a median follow-up of 55 months for the entire cohort (IQR: 37 months-62 months), the incidence of treatment failure (TF) stratified by tumor response or post-neoadjuvant pathological outcome was not significantly affected by the intensity of neoadjuvant treatment, whereas the ypTNM stage was significantly associated with the risk of treatment failure. Conclusions: In this cohort study, we provide evidence that limited or no response to intensified neoadjuvant treatment protocols is not likely to be more strongly associated with an extensive risk of TF after 5-FU CRT+/− adjuvant chemotherapy.